Phenology of the threatened species Leptocereus scopulophilus (Cactaceae) in a semi-deciduous forest of western Cuba - Toledo, Sandy; Barrios, Duniel; García-Beltrán, José Angel; González-Torres, Luis Roberto (Instituto de Ecología, A.C., 2020)
Background and Aims: Phenological studies have shown their utility in understanding the ecosystem dynamics and could be useful for the conservation of plant species. In cacti, studies evaluating reproductive and vegetative phenology are still scarce, particularly in species inhabiting semi-deciduous forest. The present study addresses different aspects of the phenology of Leptocereus scopulophilus, an endemic threatened cactus inhabiting a semi-deciduous forest of western Cuba. The main objectives of this study are to characterize the phenology of L. scopulophilus, to compare its interannual behavior in years with different rainfall regimes, and to evaluate the relationships between phenophases and environmental variables. Methods: Fifty adult individuals were selected and the number of buds, flowers, fruits, as well as vegetative growth and retrogressions of a randomly selected branch were recorded monthly for three years. The percentage of lighting, temperature, relative humidity and rainfall was evaluated monthly. The annual and interannual patterns of each phenophase were compared using circular statistics. The relationship between climatic variables and the phenophases was evaluated using a Spearman correlation. Key results: Flowering and fruiting patterns were unimodal with lagged maximums in one month. Flowering coincided with the late dry season and fruiting occurred at the beginning of the rainy season. Vegetative growth generally occurred randomly and simultaneously with reproduction, while the retrogressions occurred during the rainy season. The variable most correlated with the phenophases was lighting. Conclusions: The opening of the canopy of the semi-deciduous forest where L. scopulophilus occurs favors the reproduction and growth of its branches. This event was modulated by the duration and intensity of the rains of the previous season.